The Impacts of Perceived Organizational Support and Work Environment on Employee Performance: The Mediating Effects of Job Satisfaction - Ratnasari, Desi; Nayati Utami, Hamidah; Prasetya, Arik (Profit: Jurnal Adminsitrasi Bisnis, 2023)
One of the employees required to have optimal performance is an employee within the scope of a health service organization. There are indications of problems in the performance of non-medical health workers at Aliyah General Hospital, Kendari City, Southeast Sulawesi. Researchers built the perception that their low performance could be influenced by perceived organizational support, work environment, reward, punishment, or job satisfaction. The study was conducted at Aliyah General Hospital (1, 2, and 3) in Kendari City, Southeast Sulawesi. This study used a quantitative approach with 157 respondents. Data analysis used Partial Least Square-Structural Equation Modeling (PLS-SEM) with the help of SmartPLS 3 software. The results showed that perceived organizational support did not significantly affect employee performance and job satisfaction. In contrast, the work environment significantly affected employee performance and job satisfaction. Job satisfaction has a significant effect on employee performance. Job satisfaction cannot mediate perceived organizational support on employee performance; on the contrary, it has a mediating effect on the work environment on performance. The results of this study indicate that the performance of employees of the Aliyah General Hospital in Kendari City is driven by their work environment, especially the support of colleagues.